A Retrospective Review of Communication Evaluation Practices of Young Latinx Children. (December 2021) - Huerta, Lidia; Cycyk, Lauren M.; Sanford-Keller, Hannah; Busch, Amy; Dolata, Jill; Moore, Heather; De Anda, Stephanie; Zuckerman, Katharine
A retrospective review of initial early intervention and early childhood special education (EI/ECSE) evaluation reports was completed to identify practices specific to the evaluation of Latinx children's communication development. A records abstraction approach employed entailed a random selection of 294 EI/ECSE evaluation reports completed in Oregon with Latinx children with communication concerns. The reports were coded for documentation of background information, evaluation procedures, and eligibility decisions. Quantitative and qualitative analyses were completed to identify common evaluation practices. Adequate evaluation practices documented included the use of a multidisciplinary evaluation team, administration of multiple evaluation measures, and provision of basic information on children's language background. EI/ECSE providers did not consistently specify children's language exposure/use, denote the language of the evaluation, prioritize appropriate assessment measures, and indicate attention to cultural and linguistic differences when determining eligibility. Recommendations for decreasing bias in the evaluation of Latinx children and culturally and linguistically diverse (CLD) populations more broadly are offered.